A new approach to the effects of isocyanide (CN-R) ligands on the luminescence properties of cycloplatinated(ii) complexes. (21st November 2017) - Shahsavari, Hamid R.; Babadi Aghakhanpour, Reza; Hossein-Abadi, Mojdeh; Golbon Haghighi, Mohsen; Notash, Behrouz; Fereidoonnezhad, Masood
Abstract : Cycloplatinated complexes bearing isocyanides were prepared and characterized. The complexes exhibited strong luminescence while the nature of R substituents in isocyanides affected the luminescence characteristics. Abstract : The present investigation highlights the effects of the presence of isocyanide ligands on the emission properties of cycloplatinated(ii ) compounds. The new complexes with a general formula of [Pt(ppy)(Me)(CN-R)] (ppy = deprotonated 2-phenylpyridine and R = benzyl (1 ), 2-naphthyl (2 ), tert -butyl (3 )) were produced using a quite simple method. Then, the resulting complexes were accurately identified employing multinuclear 1D and 2D NMR spectroscopy and two of them (1 and3 ) were further authenticated by single crystal X-ray crystallography. The optical properties of1–3 were investigated by UV-visible and photoluminescence spectroscopy. The obtained photophysical data were supported by density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations. The concurrent presence of Me and isocyanide ligands as two strong carbon σ-donor ancillary ligands in the structure of these cycloplatinated(ii ) complexes was probably responsible for the strong luminescence observed at room temperature. This was confirmed by the obtained relatively high quantum yield values (0.41, 0.56 and 0.40 for1, 2 and3, respectively). The luminescence investigation of the complexes under different conditions indicates that R substituents in the structures of isocyanide ligands have a remarkable influence on the emission properties.